Habitat- and host-related variation in sponge bacterial symbiont communities in Indonesian waters - Cleary, Daniel F. R. (2018)
Marine lakes are unique ecosystems that contain isolated populations of marine organisms. Isolated from the surrounding marine habitat, many lakes house numerous endemic species. In this study, microbial communities of sponges inhabiting these lakes were investigated for the first time using barcoded pyrosequencing of 16S rRNA gene amplicons. Our main goals were to compare the bacterial richness and composition of two sponge species (Suberites diversicolor and Cinachyrella australiensis) inhabiting both marine lakes and adjacent open coastal systems. Host species and habitat explained almost 59% of the variation in bacterial composition. There was a significant difference in composition between both host species. Within S. diversicolor, there was little discernible difference between bacterial communities inside and outside lakes. The bacterial community of this species was, furthermore, dominated (63% of all sequences) by three very closely related alphaproteobacterial taxa identified as belonging to the recently described order Kiloniellales. Cinachyrella australiensis, in contrast, hosted markedly different bacterial communities inside and outside lakes with very few shared abundant taxa. Cinachyrella australiensis in open habitat only shared 9.4% of OTUs with C. australiensis in lake habitat. Bacteria were thus both highly species specific and, in the case of C. australiensis, habitat specific.